2021
DOI: 10.1080/15562948.2021.1930322
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Social Support: A Longitudinal Study of Unaccompanied Refugee Minors’ Care Networks

Abstract: Extending existing frameworks, this article examines continuities and disruptions in unaccompanied refugee minors' social support networks, their mental health impact, and what these changes mean to the young people. Interviews with 35 URMs along their trajectories in Belgium and other European countries, at three measurement moments and over a period of two years, showed that family, peers and volunteers remained central sources of social support. Contributions of formal support depended on the URMs' status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…This study's results contribute to the growing body of research on cumulative trauma in unaccompanied young refugees indicating a high and continuous trauma load in a heterogeneous sample of unaccompanied young refugees at different time points as they move through different study settings (e.g., refugee camps, detention, asylum centers), regions, and countries in Europe. Contrary to the continuous traumatization, however, the number of reported daily stressors significantly decreased over time, which may be explained by the extraordinary resilience of young refugees, often in the form of social networks [27], which might encompass a potential adaptation process to the harsh conditions they are facing on their flight [28]. Another possible explanation is that most participants in our sample journeyed from transit countries, where conditions are often extremely harsh, to settlement countries in Northern Europe, where young refugees likely face fewer daily stressors.…”
Section: Discussionmentioning
confidence: 84%
“…This study's results contribute to the growing body of research on cumulative trauma in unaccompanied young refugees indicating a high and continuous trauma load in a heterogeneous sample of unaccompanied young refugees at different time points as they move through different study settings (e.g., refugee camps, detention, asylum centers), regions, and countries in Europe. Contrary to the continuous traumatization, however, the number of reported daily stressors significantly decreased over time, which may be explained by the extraordinary resilience of young refugees, often in the form of social networks [27], which might encompass a potential adaptation process to the harsh conditions they are facing on their flight [28]. Another possible explanation is that most participants in our sample journeyed from transit countries, where conditions are often extremely harsh, to settlement countries in Northern Europe, where young refugees likely face fewer daily stressors.…”
Section: Discussionmentioning
confidence: 84%
“…We found that the number of friends in Germany was negatively associated with both depressive and posttraumatic stress symptoms. Social support is a well-established protective factor in trauma survivors ( 41 , 42 ) and previous research has stressed the importance of friendships for refugee youth ( 43 , 46 ). Some studies have suggested that ethnicity of peers and social networks may influence the effects of social support on mental health in refugee children and youth ( 40 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the number of close friends originating from Germany, in contrast to the general number of friends in Germany, was not significantly associated with mental health symptoms. A recent study with refugee youth in Belgium found that peers of similar heritage were more important in the early stages of flight, while local friends in the resettlement country became increasingly important in later stages of the resettlement process ( 43 ). Overall, this suggests that the proximity of friends in everyday life—but not ethnicity—mattered most for youth in our sample, most of whom had been in Germany for a while.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For De Graeve and Bex (2017, p. 80), 'the young people's intersectional positioning as both minor and immigrant translates into a minimalistic and bureaucratic apparatus of care that often fails to accommodate the young people's actual needs'. Moreover, although most unaccompanied minors live in large reception structures, studies have shown that smaller-scale initiatives with a higher staff ratio, such as the specialised centres set up by the Flemish-and French-speaking communities, generally provide better support for these youngsters with regards to family reunification procedures, educational trajectories, housing possibilities and job opportunities (Behrendt et al, 2021;Lietaert et al, 2020;Van Raemdonck et al, 2022). As a result of the asylum procedure, the three-phase reception system and the use of disciplinary transfers, minors also make several moves during their time within this system, starting from when they arrive in Belgium and lasting until they reach the age of majority (De Graeve & Bex, 2017, p. 83).…”
Section: Organisation Of Care For Unaccompanied Minors In Belgiummentioning
confidence: 99%